Understanding Farmers' Knowledge, Attitude, and Practices in Managing Water Quality for Effective Insecticide Performance: A Case Study in Agriculture - Sanaullah Mangi; Fahad Nazir Khoso; Arfan Ahmed Gilal; Muhammad Javed Sheikh (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Pesticides are frequently used in agriculture to manage pest populations below threshold levels, but their application usually does not get the desired outcome. There are many factors for the low performance of pesticides, with water quality being one of them. Local farmers from Sindh, Pakistan, have little or no knowledge about the role of water quality in the performance of pesticides. Therefore, a survey study was conducted to determine the farmer’s knowledge, attitude, and practice regarding it. Ten villages were selected from the Hyderabad and Tando Allahyar districts, and the information was obtained from five farmers from each village. Descriptive analysis results indicated that most respondents prefer to grow cotton (average 24.07 acres), with the majority being illiterate (54 %), averaging 39.74 years of age and 18.80 years of farming experience. Most farmers (92 %) used groundwater for spray solution, whereas only 3 % tested the water in their fields. The majority (74.51 %) of farmers considered lower-quality pesticides for their poor performance. Therefore, farmers normally apply up to sixteen sprays to control pests. It was also observed that although farmers have knowledge about the role of water quality in the performance of pesticides to get pest control, they lack the attitude and practice in their field. Therefore, it is suggested that awareness should be created among the local farmers regarding water quality to be used in spray solutions to get desired pest control.